Assessing Differences in Concussion Symptom Knowledge and Sources of Information Among Black and White Collegiate-Athletes. Issue 3 (May 2021) - Wallace, Jessica; Beidler, Erica; Kerr, Zachary Y.; Hibbler, Tamaria; Anderson, Morgan; Register-Mihalik, Johna K.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: Basic concussion symptom knowledge is fundamental to concussion identification; however, racial disparities in concussion knowledge exist in high school and youth sports. It is unknown whether similar differences exist in collegiate-athletes. Identifying racial disparities in concussion knowledge and sources of concussion information is essential to inform equitable approaches to knowledge translation and educational interventions. This study examined how Black and White collegiate-athletes differed in their knowledge of concussion symptoms and use of concussion information sources. Setting: National Collegiate Athletic Association (NCAA) institutions. Participants: Collegiate-athletes. Design: Cross-sectional. Main Measures: Collegiate-athletes completed a questionnaire that assessed personal and sports demographics, concussion symptom knowledge, and use of concussion information sources. Fisher's exact tests and Wilcoxon rank-sum tests examined differences in outcome measures between Black and White collegiate-athletes. A multivariable Poisson regression model examined the association between race and concussion symptom knowledge scores while accounting for sex, sports contact level, NCAA division, concussion history, and specific concussion information sources. Incidence rate ratios (IRRs) with 95% CIs excluding 1.00 were deemed significant. Results: A total of 768 (82.6% White, 17.4% Black) collegiate-athletes completed the questionnaire. Black athletes were more likely to have lower concussion symptom knowledge scores than White athletes ( P < .001). In the multivariable Poisson regression model controlling for covariates, this finding was retained (IRR = 0.97; 95% CI, 0.94-0.997). White athletes were more likely to report school-based professional ( P < .001), online medical sources ( P = .02), and the NCAA ( P = .008) as sources of concussion information. Black athletes were more likely to report referees ( P = .03) as a source of concussion knowledge. Conclusion: Despite NCAA concussion education requirements for athletes, Black collegiate-athletes were found to have lower concussion knowledge than White collegiate-athletes. The findings highlight the need for equitable strategies to disseminate concussion information to diverse populations by improving the physician-patient relationship and investing in culturally appropriate educational materials.